Brain connectivity changes during ictal aggression (a strangulation attempt). Issue 3 (31st October 2017) - Bartolomei, Fabrice; Lagarde, Stanislas; Lambert, Isabelle; Trébuchon, Agnes; Villalon, Samuel Médina; McGonigal, Aileen; Benar, Christian G
Abstract: Ictal aggressive behaviour is a rare manifestation of focal seizures. We report an episode of ictal aggression occurring during an intracerebrally recorded seizure (using stereoelectroencephalography) in a patient with drug‐resistant temporal lobe epilepsy. Aggression occurred during the last part of the seizure and was coincident with marked EEG slowing of the frontal regions and persistent ictal activity in the medial temporal lobe. A functional connectivity study (h 2 estimation of interdependencies) showed a bilateral massive hypersynchronization between frontal and temporal regions. This case illustrates the occurrence of aggression during imbalance between the electrical activity in the temporal limbic cortex and prefrontal cortex, in agreement with the current neurobiological theories of aggression.